2000
DOI: 10.1902/jop.2000.71.3.368
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activity of a Monoclonal Antibody Against a Recombinant 40‐kDa Outer Membrane Protein of Porphyromonas gingivalis

Abstract: Pg-ompA2 has an in vitro complement-mediated bactericidal activity to P. gingivalis. Pg-ompA2 may contribute to the development of a local immunotherapy that can be applied in the gingival crevice of a patient with P. gingivalis-related periodontitis, or be a vaccine candidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…However, the role of Fc␣RI and Fc␥RI in the pathogenesis of periodontitis remains unclear. As an approach to enhancing anti-P. gingivalis PMN function or to inhibiting colonization, major attention has been focused on local passive immunization with polyclonal antibodies or monoclonal antibodies (MAb) (3,28,47). It is therefore important to clarify the relative contributions of IgG and IgA receptors in triggering the anti-P. gingivalis function of GCF PMN.…”
mentioning
confidence: 99%
“…However, the role of Fc␣RI and Fc␥RI in the pathogenesis of periodontitis remains unclear. As an approach to enhancing anti-P. gingivalis PMN function or to inhibiting colonization, major attention has been focused on local passive immunization with polyclonal antibodies or monoclonal antibodies (MAb) (3,28,47). It is therefore important to clarify the relative contributions of IgG and IgA receptors in triggering the anti-P. gingivalis function of GCF PMN.…”
mentioning
confidence: 99%
“…In this regard, it has been shown that 40k-OMP-specific rabbit monoclonal antibodies inhibit coaggregation activity of P. gingivalis (14,16,20). Further, these monoclonal antibodies possess complement-mediated bactericidal activity to P. gingivalis (17,18). Moreover, a recent study has demonstrated that these antibodies have opsonic activity on human neutrophil function for phagocytosis of P. gingivalis (19).…”
Section: Discussionmentioning
confidence: 99%
“…Further, these monoclonal antibodies possess a complement-mediated bactericidal activity to P gingivalis (17,18). It has also been demonstrated that anti40k-OMP antibody opsonizes P gingivalis as a target for phagocytosis by the human neutrophil cell line (19).…”
Section: Introductionmentioning
confidence: 99%
“…Polyclonal anti-40 kDa.. OMP antibody exhibited potentially protective, complement-mediated bactericidal effect. 12 Gingipains [13], [14] Coined by Travis and Colleague These are cysteine proteinases which cleave synthetic and natural substrates after arginine or lysine residues and are referred to as arginine gingipain (Rgp) and lysine gingipain (Kgp), respectively.…”
Section: Outer Membrane Proteinmentioning
confidence: 99%